SISTEM PAKAR TINGKAT STRES PADA MAHASISWA SKRIPSI BERBASIS WEBSITE (STUDI KASUS: FAKULTAS TEKNIK UNIVERSITAS PALANGKA RAYA) - Putu Atika; Abertun Sagit Sahay; Nahumi Nugrahaningsih; Ariesta Lestari; Felicia Sylviana (Jurnal Teknologi Informasi: Jurnal Keilmuan dan Aplikasi Bidang Teknik Informatika, 2023)
An expert system is an application program that tries to imitate the reasoning of an expert in solving a problem. Students at the Faculty of Engineering who are taking a thesis must have experienced stress when working on a thesis, this is obtained from internal and external factors, stress is divided into 4, namely normal, mild, moderate, and severe stress. To find out what level of stress they are experiencing while working on the thesis. Therefore, in this thesis research, we will discuss how to design and build an Expert System application for Stress Levels for Website-Based Thesis Students (Case Study: Faculty of Engineering, University of Palangka Raya) aims to create an expert system using the forward chaining method and certainty factor, by making an application. In this way, students can find out the level of stress that is being experienced when working on a thesis and be given solutions according to the level of stress. The result is an expert system application that can replace the presence of experts to diagnose stress levels. Students make independent diagnoses by answering the symptoms they are experiencing. This study uses 10 student data from the Department of Civil Engineering 3, Architecture 2, Informatics Engineering 3, and Mining Engineering 2. The results can be concluded that the dominant students experience severe stress levels when working on theses. There is a recapitulation to see the percentage of students who experience stress levels at stress levels and periods.